Daya Dukung dan Penurunan Pondasi pada Pesisir Pantai Timur Kabupaten Bangka - Ferra Fahriani; Yayuk Apriyanti (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2020)
A Construction of buildings on the beach is needed to provide facilities and infrastructure. An analysis of bearing capacity and foundation settlement for building construction is necessary to avoid structural failure. This study analyzed bearing capacity and foundation settlement on the East coast of Bangka Regency, Bangka Belitung Island Province, including Tikus Beach, Takari Beach and Karang Mas Air Anyir Beach, based on field data from Cone Penetration Test (CPT). Result showed that the level of soil consistency, bearing capacity, and foundation settlement can be analyzed by combining the structural loads for the 1 to 5 floor buildings. Bearing capacity of shallow foundation was calculated using the Meyerhof (1976) method, whereas the deep foundation is using the Meyerhof (1956) method. Settlement of shallow foundation was calculated using the Steinbrenner (1934) method, whereas the deep foundation is using the Vesic (1970) method. This study found the soil consistency levels at three locations had the range from medium to hard level. The analysis of foundation bearing capacity showed that the greater of soil bearing capacity, the smaller of foundation dimensions. The greater the load that must be held by the foundation, the greater the size of the foundation needed to withstand it. The analysis of the settlement showed that the smaller of the soil bearing capacity, the greater of settlement. The greater the load that must be withheld by the foundation, the foundation settlement will greater.